Construction of a prognostic model via WGCNA combined with the LASSO algorithm for stomach adenocarcinoma patients - Huang, Zi-duo; Ran, Wen-hua; Wang, Guo-zhu (Frontiers in Genetics, 2024)
Objective: This study aimed to identify prognostic signatures to predict the prognosis of patients with stomach adenocarcinoma (STAD), which is necessary to improve poor prognosis and offer possible treatment strategies for STAD patients.The overlapping genes between the key model genes that were screened by the Weighted Gene Co-expression Network Analysis (WGCNA) and differential expression genes (DEGs) whose expression was different with significance between normal and tumor tissue were extracted to serve as co-expression genes. Then, those genes were performed enrichment analysis. Furthermore, the Least Absolute Shrinkage and Selection Operator regression (LASSO) was performed to screen the 2 hub genes among overlapping genes. Lastly, we constructed a model to explore the influence of polygenic risk scores on the survival probability of patients with STAD, and interaction effect analysis and mediating analysis were also performed.The DEGs included 2899 upregulated genes and 2896 downregulated genes. After crossing the DEGs and light-yellow module genes that were obtained by WGCNA a total of 39 overlapping genes were extracted. The gene enrichment analysis revealed that these genes were enriched in the prion diseases, biosynthesis of unsaturated fatty acids, RNA metabolic process, hydrolase activity, etc. PIP5K1P1, PTTG3P, and SNORD15B were determined by LASSO-cox. The prognostic prediction of the 3 genes model was established. The Cox regression analysis showed that the comprehensive risk score for 3 genes was an independent prognosis factor. Conclusion: PIP5K1P1, PTTG3P, and SNORD15B are related to the prognosis and overall survival of patients. The 3 genes risk model constructed has an independent prognosis predictive ability for STAD.